EDUKASI DAN PRAKTIK CUCI TANGAN UNTUK ANAK USIA PRASEKOLAH DI TK NIDZAMYAH KOTA KEDIRI - Wahyuni, Ida Tri; Rohmawati, Huda; Lutfiasari, Dessy; Sabda Nirwana, Betanuari (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Abstract Preschool children’s health is strongly influenced by clean and healthy living habits, one of which is handwashing. However, many children still do not understand the importance of proper handwashing. This community service program aimed to improve the knowledge and skills of children aged 4–6 years in practicing handwashing according to WHO standards. The activity was carried out on July 19, 2025, at TK Nidzamyah, Campurejo Subdistrict, Kediri City, involving 53 preschool children, 6 teachers, and 40 parents/guardians. The implementation methods included interactive health education, a demonstration of the six handwashing steps, hands-on practice by the children, and the provision of educational media in the form of posters and children’s songs. Teachers and parents were also given supporting materials to continue the education in their respective settings. The results showed that more than 88% of the children were able to perform proper handwashing after the education session, and there was an increase in parents’ awareness of the importance of establishing clean-living habits from an early age. This program had a positive impact not only on children’s behavior but also on enhancing collaboration between teachers and parents in supporting handwashing routines. With a fun and educational approach, this initiative can serve as an effective promotive intervention model in other early childhood education settings. Keywords: Handwashing; Preschool children; Health education